Arsenic and smokeless tobacco exposure induces DNA damage and oxidative stress in reproductive organs of female Swiss albino mice. (9th December 2020) - Nath Barbhuiya, Sweety; Barhoi, Dharmeswar; Giri, Anirudha; Giri, Sarbani
Abstract: Arsenic contamination in the groundwater of Southern Assam, India is well-documented. A specific type of smokeless tobacco ( sadagura, SG) is highly prevalent among the local population. Thus, the present study is aimed to evaluate the toxicological implications of arsenic and smokeless tobacco co-exposure on the reproductive health of female mice. The estrous cycle of experimental animals was monitored for 30 days. Histopathological studies and comet assay of ovarian and uterine tissues were performed after 30 days of exposure to SG and arsenic (sodium arsenite, SA). Oxidative stress was estimated biochemically by taking tissue glutathione, lipid peroxidation (LPO), and superoxide dismutase activity as endpoints. Our findings indicated a prolonged diestrus phase in the SG + L + SA group ( p  < 0.001). Histopathological study revealed abnormal tissue architecture in treated groups. Comet assay study showed that SG + SA exposure significantly induced DNA damage in test animals. The elevated LPO level in the SG + SA group indicated oxidative stress generation in the reproductive tissues. The present study suggests that female reproductive organs are vulnerable to SA and SG and oxidative stress generation may be the possible mechanism behind DNA damage, impaired follicular growth, atresia, and altered estrous cycle in the mice test system. Graphical Abstract: